1982
DOI: 10.1055/s-0038-1657255
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Thrombolytic Treatment with Porcine Plasmin and Low Dose Streptokinase

Abstract: SummaryIn the sequential thrombolytic therapy with porcine plasmin and low dose streptokinase side effects are mainly due to bleeding, intolerance reactions are less important. Treatment had to be prematurely stopped in 42 (37%) of 114 DVT cases because of severe bleeding and in 12 (10%) due to intolerance reactions. The corresponding figures for the 45 cases with arterial occlusions are 15 (33%) and 2 (4%) respectively. The intensity of systemic proteolysis as represented by the thromboplastin time is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…An important fact to note, however, is that the incidence of intracerebral hemorrhage in patients with noncerebrovascular occlusions treated with these medications is approximately 3%. 96 ' 97 In contrast, a recent report suggested that tissue plasminogen activator may lyse experimental cerebral emboli without increasing the risk of hemorrhagic infarction. 98 Despite the substantial improvement in neurologic outcome of treated animals, however, no difference in size or distribution of histologic infarction was noted between treated and control groups.…”
Section: Systemic Supportivementioning
confidence: 99%
“…An important fact to note, however, is that the incidence of intracerebral hemorrhage in patients with noncerebrovascular occlusions treated with these medications is approximately 3%. 96 ' 97 In contrast, a recent report suggested that tissue plasminogen activator may lyse experimental cerebral emboli without increasing the risk of hemorrhagic infarction. 98 Despite the substantial improvement in neurologic outcome of treated animals, however, no difference in size or distribution of histologic infarction was noted between treated and control groups.…”
Section: Systemic Supportivementioning
confidence: 99%
“…Streptokinase Infusion.-After receiving 3,000 units of por¬ cine heparin IV, each patient with a negative skin test received 750,000 IU of streptokinase by IV infusion over a period often to 15 Accepted for publication May 13,1985 Levels of IgE to streptokinase, as determined by enzyme-linked immunosorbent assay at 1:100 serum dilution. Patient 1 had positive streptokinase skin test and was treated with urokinase for myocar¬ dial infarction.…”
Section: Methodsmentioning
confidence: 99%
“…The risks of bleeding increase with duration. 49 However, it must be kept in mind that incomplete lysis of venous thrombi will not prevent the postthrombotic syndrome.…”
Section: Treatment Durationmentioning
confidence: 99%
“…Our successive treatment series with SK alone or combined with plasmin 48 clearly showed a rela tionship between intensity of fibrinolysis, success rate, and, unfortunately, bleeding complications. 49 It was expected that the anisoyl-protected SK-Plg complex (BRL 26,921, Beecham) would con siderably reduce the fibrinolytic effect in circulating blood. There is no doubt that this compound has a thrombolytic effect in rabbits 98 and a lower fibrino-lytic action in humans than SK.…”
Section: Dvt Treatment Schemesmentioning
confidence: 99%
See 1 more Smart Citation